Program Pengabdian Masyarakat Untuk Edukasi Dan Deteksi Dini Dislipidemia Dan Obesitas - Martin, Alfianto; Setia, Nicholas; Jap, Ayleen Nathalie (Institut Teknologi dan Bisnis Semarang, 2024)
Dyslipidemia in the elderly is a serious condition characterized by high or low levels of lipids in the blood, including cholesterol and triglycerides, which increases the risk of cardiovascular disease. In this community service activity, education and health checks were carried out on 94 elderly people at the Bina Bhakti Nursing Home. The results showed that 90.3% of elderly people had normal cholesterol levels, while 9.7% had dyslipidemia. As many as 62.4% had optimal HDL levels, but 37.6% had non-optimal HDL levels. Regarding LDL parameters, 62.4% had optimal levels and 37.6% did not have optimal levels. Dyslipidemia was more common in elderly women (10.8%) than men (5.3%). Modifiable risk factors such as diet and physical activity greatly influence blood lipid levels. Education regarding the importance of a healthy diet and regular health checks is very necessary to manage dyslipidemia in the elderly. This activity emphasizes the importance of a comprehensive educational approach and program to reduce the prevalence of dyslipidemia and improve the quality of life of the elderly. Keywords: Education, Hyperlipidemia, Cardiovascular, Elderly, Screening